A new HLA‐B*55 allele, B*55:83N with a stop codon in exon 4 generated by a point mutation, identified in a Chinese individual. (February 2017) - Zhou, X.‐Y.; Jiang, P.; Zhang, L.‐Q.; Cui, J.; Cai, J.‐P.
Abstract : The new allele HLA‐B*55:83N differs from HLA‐B*55:02:01:01 by a single nucleotide.